Cryptogenic Organising Pneumonitis: A Clinical Case of A Recurrent Pneumonia (Archives of Clinical and Medical Case Reports, 2019)
Organising pneumonia (OP) is a clinical, radiological and histopathological entity with unknown etiology, previously named bronchiolitis obliterans with organising pneumonia. A 74-year-old female, presented with asthenia and dyspnea. In the three days before she was on levofloxacin without benefit. She had a previous history of breast cancer and arterial fibrillation under daily amiodarone. During the year before she was three times hospitalized with pneumonia with a weak response to treatments and relapse after apparent resolution. She was re-hospitalized with community acquired pneumonia (CAP) diagnosis having, again, poor response to antibiotics. As there were no clinical or radiological improvements, a chest computed tomography (CT) scan was performed showing diffused pulmonary condensations with air bronchogram. Cryptogenic organizing pneumonia (COP) diagnosis was confirmed through a transbronchial lung biopsy (TLB). This diagnosis difficulty was increased by the interference of concomitant amiodarone intake or even by paraneoplastic hypothesis due to previous breast cancer history, which had to be promptly excluded. Corticotherapy allowed sequential radiological pattern normalization, clinical and analytical improvement. In recurrent pneumonia cases, COP must be considered and further diagnostic tools should be used.